A Case of Abdominal Discomfort for Long Duration (Bangladesh Critical Care Journal, 2024)
In our regular medical practice, we encounter a lot of patients with abdominal discomfort. Commonly every physician suspects this kind of symptoms as gaseous distension of gastro-intestinal tract or acidity. The most valuable thing is the proper physical examination to rule out any underlying pathology. Most common causes of epigastric pain are associated with gastritis, or hepatobiliary system and pancreas related disorders. Here we will describe a 47-year-old male patient who presented with abdominal discomfort for last 6 months. For last 2 months he developed an epigastric lump which was increasing in size and was associated with weight loss. After proper clinical evaluation and necessary relevant investigations, he was diagnosed having Non-Hodgkin’s Lymphoma (NHL). Non-Hodgkins Lymphoma represents monoclonal proliferation of lymphoid cells. The incidence of these tumors increases with age. Clinically the proliferation rate indicates whether it is a high- or low-grade tumor. The patient underwent some investigations like CT guided FNAC from the enlarged abdominal lymph node which confirmed high grade Non-Hodgkins Lymphoma and started with chemotherapy and responded well.As abdominal discomfort is one of the common complaints, we face during our regular medical practice so routine physical examination including abdominal examination is very crucial and informative for clinical diagnosis and Lymphoma is an important differential diagnosis in case of any abdominal lump.Bangladesh Crit Care J September 2024; 12 (2): 175-178